PENGARUH CONTENT MARKETING, PRICE DISCOUNT DAN LIVE STREAMING TERHADAP IMPULSIVE BUYING PADA TIKTOK SHOP (STUDI KASUS PADA AKUN LOUISSESCARLETT) - Angelina, Jessica; wijaya, Shierli (Publika Citra Media, 2025)
In this digital era, TikTok Shop has become a strategic platform that stimulates impulsive buying behavior through its interactive features. The Louissescarlett account was chosen as the subject of this study due to its proven success in implementing effective marketing strategies, including engaging content creation, discount offers that create a sense of urgency, and interactive live streaming sessions. This research aims to examine the impact of Content Marketing, Price Discounts, and Live Streaming on impulsive buying behavior on TikTok Shop, using the Louissescarlett account as a case study.This study utilizes a quantitative approach with a survey method. Data were gathered through an online questionnaire from 160 respondents who met the specified criteria, namely active TikTok Shop users who had previously purchased from the Louissescarlett account. Multiple linear regression analysis was used to determine the effect of the independent variables on the dependent variable. The findings indicate that Content Marketing, Price Discounts, and Live Streaming significantly and positively influence impulsive buying behavior, both individually and collectively. The combination of these variables plays a crucial role in driving consumers to make spontaneous purchase decisions. These results offer practical insights for businesses to develop more effective marketing strategies on social media platforms and provide theoretical contributions to digital marketing and consumer behavior research.